BiW8O30 Exerts Antitumor Effect by Triggering Pyroptosis and Upregulating Reactive Oxygen Species. (20th August 2021) - Jia, Di; Gong, Lige; Li, Ying; Cao, Shu; Zhao, Weiming; Hao, Lijun; Li, Shasha; Pang, Bo; Zhang, Chunjing; Li, Shuyan; Zhang, Wei; Chen, Tianyi; et al.
Abstract: We successfully synthesized BiW8 , a 10‐nuclear heteroatom cluster modified BiW8 O30 . At 24 h post‐incubation, the IC50 values of BiW8 against HUVEC, MG63, RD, Hep3B, HepG2, and MCF7 cells were 895.8, 127.3, 344.3, 455.0, 781.3, and 206.3 μM, respectively. The IC50 value of BiW8 on the MG63 cells was more than 2‐fold lower than that of the other raw materials. Through morphological and functional features, we demonstrated pyroptosis as a newly identified mechanism of cell death induced by BiW8 . BiW8 increased 2‐fold reactive oxygen species (ROS) levels in MG63 cells at 24 h post‐incubation. Compared with 0 h, the glutathione (GSH) content decreased by 59, 65, 75, 94, and 97 % at 6, 12, 24, 36 and 48 h post‐incubation, respectively. Furthermore, multiple antitumor mechanisms of BiW8 were identified via transcriptome analysis and chemical simulation, including activation of pyroptosis, suppression of GSH generation, depletion of GSH, and inhibition of DNA repair. Abstract : We successfully synthesized BiW8 , a 10‐nuclear heteroatom cluster modified BiW8 O30 . BiW8 suppressed the proliferation, migration, and invasion of MG63 cells. We identified POM‐induced pyroptosis for the first time. Decreased GSH content and increased ROS levels were observed in BiW8 ‐treated cells. BiW8 executed multiple antitumor mechanisms, such as activation of pyroptosis, regulation of oxidative stress, and inhibition of DNA repair.